PENERAPAN TEKNIK ELEKTROLISIS BIPOLAR UNTUK ELEKTROSINTESIS KOBAL (III) ASETAT DALAM LIMBAH ARTIFISIAL INDUSTRI FENOL - (NIM : 25399001), Amirichanto
Abstract : Cobalt (III) acetate is an oxidizing agent and an important catalyst which is used in organic and hydrocarbon industries. Generally, waste produced at the end of the process included cobalt (II) acetate that mixed with water and salt alkali. One of the alternatives to handle waste pollution problem in industry is to oxidize cobalt (II) acetate becomes cobalt (III) acetate thus they can be reused as oxidator or catalyst. Bipolar electrolysis technique has been studied in this research, using packed-bed flow reactor to recovery cobalt(III)acetate from cobalt(II)acetate artificial waste. Bipolar cell was arranged from three-dimensional graphite disc within 35 layers. Determination of optimum condition of potential cell electrode, flow rate, pH electrolyte influence, and electrolyte concentration have been done for reactor characterization. The result of experiments show that optimum cobalt (III) acetate on electrolyte concentration is 0,2 M CH3COOH.3H2O, pH=1 ,77 with conversion ratio is 55,63%, space-time yield 120,36 Kg.m-3.h-1 and energy consumption is 63,08 KWh.kg-1 on flow rate 0,180 L.h and potential per cell 7,14 Volt.